Comparison of dissipation models for irregular breaking waves - Winyu Rattanapitikon; Romanee Karunchintadit (Songklanakarin Journal of Science and Technology (SJST), 2002)
The irregular wave height transformation has been a subject of study for decades because of itsimportance in studying beach deformations and the design of coastal structures. The energy dissipation isan essential requirement in the computation of wave height transformation. During the past few decades, many dissipation models have been developed, for regular wave see Rattanapitikon and Leangruxa (2001). This study is undertaken to examine the accuracy of 7 existing dissipation models for irregular breaking waves, i.e., the models of Battjes and Janssen (1978), Thornton and Guza (1983) (2 models), Battjes and Stive (1984), Southgate and Nairn (1993), Baldock et al. (1998), and Rattanapitikon and Shibayama (1998).The coefficients of the models are re-calibrated and the overall accuracy of the models is compared. A large number and wide range of wave and bottom topography conditions (total 385 cases from 9 sources ofpublished laboratory data) are used to re-calibrate and compare the accuracy of the 7 models. It appears that the model of Rattanapitikon and Shibayama (1998) gives the best prediction for general cases.